A founding mother : a novel of Abigail Adams - Dray, Stephanie; Kamoie, Laura Croghan (William Morrow and Company, 2026)
"In the heart of revolutionary Boston, Abigail Adams raises her children amid riots, blockades, and the outbreak of war. While her husband, John Adams, rises from country lawyer to nation-builder, often away for years at a time, Abigail builds her own independence--managing their farm, making lucrative investments, amassing savings, battling plaque and loss, and defending their home. Unafraid to speak her mind, she famously offers fearless political counsel, urging John to "remember the ladies" in the new government. Through it all, she becomes his most trusted confidante and indispensable ally. When peace is secured, Abigail steps onto the world stage--exchanging ideas with Thomas Jefferson in the French countryside, navigating court life as the wife of the Minister to Great Britain, and presiding over the parlor politics of the early American republic in New York, Philadelphia, and Washington, DC. Even after her husband's presidential administration, she continues battling political foes and working behind the scenes to advance her family, secure independence for the women in her life, and ensure a better life for the next generation of Americans." --